The wire. The complete fifth season [videorecording (DVD)] - Simon, David, 1960-; West, Dominic, 1969-; Akinnagbe, Gbenga; Cathey, Reg E.; Crawford, Jermaine, 1992-; Doman, John, 1945-; Gillen, Aidan, 1968-; Hector, Jamie; Huff, Neal; Johnson, Clark, 1954-; Lovejoy, Deirdre, 1962-; McCarthy, Tom, 1966-; et al. (HBO Video, 2008)
Follows a single sprawling drug and murder investigation in Baltimore. Told from the point of view of both the police and their targets, where easy distinctions between good and evil are challenged at every turn.